Khuruj Fi Sabilillah Jama'ah Tabligh: Fulfilment of Alimony, Implications for Household Harmony and Wife Psychology - Setiawan, Agus; Asnawi, Habib Shulton Asnawi (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2023)
This article reveals the household conditions of the Tabligh Jama'ah in the context of fulfilling the husband's livelihood towards his wife. The fulfilment of livelihood in the Tabligh Jama'ah is interesting to study because the followers of Jamâ'ah Tabligh apply a pattern that is often done, namely Khuruj Fi Sabilillah. The purpose of this article is how is the practice of fulfilling husband's alimony to his wife in Tabligh Jama'ah and its impact on the household from the perspective of wife's psychology? The type of this article is qualitative, analysing in depth related to the fulfilment of maintenance and wife psychology with the aim of revealing the practice of fulfilling the husband's maintenance obligations towards the wife of Jamâ'ah Tabligh, this field research was conducted in Metro City, the primary data source of this article is the husband of Jamâ'ah Tabligh followers and the wife left behind by her husband Khurûj f? sab?lillah. The results of the study found that the fulfilment of maintenance for Tabligh followers in Metro City who perform Khuruj Fi Sabilillah to provide maintenance for their wives is divided into three categories; first, well fulfilled, second less fulfilled, and third unfulfilled. However, the practice of Khuruj Fi Sabilillah causes a lot of household disharmony because the maintenance is not fulfilled, this has an impact on the wife's mental psychological burden, because the wife has to play a dual role, taking care of household affairs while earning a living.